How Are Argentina and Chile Facing Shared Biodiversity Loss? - Estenssoro-Saavedra, J (SPRINGER, 2018)
Biodiversity loss remains one of the most pressing issues for global governance. This situation can be seen in Argentina and Chile through the effects of biodiversity loss caused by the introduction and expansion of beavers in Southern Patagonia. This case is interesting because, despite the Beagle conflict (i.e., the border dispute) between these countries some decades ago, nowadays Argentina and Chile are facing shared environmental problems and both are actively seeking solutions. The main question in this paper is, how did Argentina and Chile search for a solution to shared environmental problems caused by the expansion of beavers in Southern Patagonia? This paper tackles this question and presents the results of the conducted qualitative research. The results indicate that, in order to understand what Argentina and Chile are doing to achieve a solution to their shared environmental problems, research cannot be exclusively focus on domestic affairs. Instead, this issue requires taking into account how international dimensions influenced domestic policies. As this paper argues, in Argentina and Chile, international cooperation is a method of influencing biodiversity governance through funds granted by international organizations and international expert recommendations.